Storage Behavior of Fresh Fruits and Vegetables: A Review (International Journal of Food and Nutritional Sciences, 2022)
The majority of fresh fruit and vegetable kinds may be produced in India because to itsvaried environment (Mansuri, 2017). According to the National Horticulture Database, 2019-20 estimates put the nation's fruit and vegetable production at 97.97 million tones and 183.17million tones, respectively.